Short chain fatty acids and its producing organisms: An overlooked therapy for IBD? - Deleu, Sara (EBioMedicine, 2021)
The gut microbiome and the intestinal immune system are driving contributors to inflammatory bowel diseases (IBD). Both have an important signalling factor in common: short-chain fatty acids (SCFAs). SCFAs (acetate, propionate and butyrate) are produced by bacterial fermentation in the gut and exert several effects on host metabolism and immune system. This review provides an overview of the current knowledge of these effects, with specific focus on energy metabolism, intestinal barrier, immune system, and disease activity in IBD. To conclude, more research is needed on the cross-feeding mechanisms in the gut microbiome, as well as on the therapeutic potential of SCFAs on different disease models. Also randomized controlled trials and prospective cohort studies should investigate the clinical impact of SCFA administration.